Determinants of Foreign Direct Investment: New Granger Causality Evidence from Asian and African Economies - Awolusi, Olawumi D; Pelser, Theuns G; Adelekan, Adedeji Saidi (Journal of Economics and Behavioral Studies, 2016)
Previous studies on the determinants of foreign direct investment (FDI) have predominantly focused on developed and emerging economies. However, there seem to be few studies concentrating on a comparative analysis of vast African and Asian countries. This paper analysed drivers of foreign direct investments (FDI) to Asian and African economies using a panel dataset from 1980 to 2013.This study used Granger causality test, under vector error correction modelling (VECM) to test for causality among the variables. While the drivers of FDI inflows were measured using five dimensions as proposed by Anyanwu; the dependent variable, FDI inflows, was proxied by the ratio of FDI flows to gross domestic product (GDP). Findings revealed that variables manifesting the determinants of FDI inflows positively affected FDI into these continents. Specifically, factors such as trade openness, macroeconomic condition, infrastructural development, and monetary union have positive and significant effect on FDI to Asian economies. No significant relationship was found between FDI inflows and market size to the Asian continent during the study period. On the other hand, trade openness, macroeconomic condition, market size and infrastructural development have positive and significant effects on FDI inflows to African economies although there was no significant relationship between FDI inflows and monetary union to the African continent during the study period. In fact, there were bi-directional relationships between FDI inflows and some of the determinants in both continents. Theoretically, this model provides predictive implications on improved FDI inflows, given the activities of critical variables manifesting as determinants of FDI inflows.